Extensores alternativos na produção de adesivo para a manufatura de compensados - Luz, Marco Antonio Pepe (2015)
The objective of this work was to evaluate the use of alternative extenders as substitutes for wheat flour in the manufacture of plywood. The panels were produced with Pinus oocarpa veneers, with thickness of 2 millimeters, and glued with phenol-formaldehyde based adhesive, applied in simple line at 180 g.m-². The following extenders were used: tire ash; gray phyllite; Kraft lignin; microsilica; and white grouting. The panels were all compared to the control samples produced with wheat flour. The following physical and mechanical tests were performed in the specimen: specific mass; water absorption; swelling thickness; static bending; and glue line shear strength. Sample panels produced with white grouting provided all the minimum values specified in the reference standards, only differing statistically for glue line shear strength values at dry condition, which were above those found for control sample. However, we applying tire ash and microsilica as extenders, we verified satisfactory results for all testes, with the exception of elasticity modulus in the direction perpendicular to the fibers. These results indicate that this plywood should be used in the direction parallel to the fibers. Thus, the use of these extenders is feasible as possible substitutes for wheat flour.